The syntheses of polymethoxy flavonoid glycosides from apigenin and diosmetin and their cytotoxic activities on two human cancer cell lines - Van-Son Nguyen; Nguyen Minh Duc; Vo Thanh Cong; Son Quynh Thai Pham (Results in Chemistry, 2022)
The syntheses of a series of polymethoxy flavonoids glycosides were performed via reactions of bromination, Ullmann aromatic nucleophilic substitution, O-methylation, dimethyldioxirane (DMDO) oxidation, glycosidation and then deprotected, starting from abundant and inexpensive natural sources Apigenin and Diosmetin. This new synthetic route has many advantages such as easy availability of starting materials, simple performance, and good yields. All the compounds were tested for their anticancer activities against breast cancer (MCF-7) and HeLa cancer cell lines using CCK-8 assay. The results showed that most of the target compounds exhibited moderate to potent antiproliferative activities on MCF-7 and HeLa cells compared to the positive control cis-platin. Polyethoxy flavonoids glycosides (PFG) have been shown to improve the proliferation inhibitions on HeLa and MCF-7 cells as well as increase the water solubilities in comparison to those of polymethoxy flavonoids. The structures of the synthesized compounds have also been determined using NMR (1H, 13C), MS and HRMS.